PENGEMBANGAN E-BOOK MATEMATIKA BERBASIS MASALAH PADA MATERI KUBUS DAN BALOK SMP/MTS KELAS VIII - Alfian Bayani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2019)
The purpose of this study was to produce mathematical E-books based on the problem of cube and class VIII SMP / MTs material. This mathematical E-book development uses the Four-D development model. The model consists of 4 stages, namely, Define, Design, Develop, and Disseminate. This E-book was validated by three validators including one media expert, one material expert, and one junior high school math teacher. After the E-book was declared valid, then it is tested to students. The test subjects for the development of E-books were limited trial subjects, namely six students of class VIII at Al Maarif 01 Islamic Junior High School Singosari. The trial was conducted to determine the feasibility of E-books to be used in the learning process. Based on the results of expert and practitioner validation data analysis, overall the developed E-book was declared valid with the results of the average rating of 3.29 and fulfilling the validity criteria set. Whereas in user trials, E-books were declared valid by obtaining an average score of 3.29. Based on the results of the analysis, it can be concluded that the E-book has met the criteria eligible for use in the learning process.